Experimental Investigation on the Tensile Strength of Composite Laminates Containing Open and Filled Holes - Fan, X.L.; Qin, W.J.; Suo, T. (Проблемы прочности, 2014)
An experimental study is performed to evaluate the effects of clamping pressure, friction, and washer size on the static performance of composite laminates with open and bolt-filled holes. The static tensile strength and failure behavior of composite laminates with an open hole and a bolt-filled hole are analyzed and compared. Experimental results show that the static tensile strength of composite laminates is sensitive to pre-existing damage of both open- or filled-hole laminates. In contrast, a comparison between the experimental results of open- and filled-hole specimens proved that whether the hole is open or filled has a feeble influence on the tensile-tensile fatigue strength of studied composite laminates. In comparison, however, it is found that the inserted washer size, bolt clamping force, and friction force strongly affect the tensile strength of open- and filled-hole composite laminates. Moreover, application of thicker washers and hi-lock bolt will significantly increase the static strength and fatigue life of composite laminates with a bolt-filled hole.